2020
DOI: 10.1055/s-0040-1710565
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Surgical Repair of Medial Meniscal Root Tears: A Review

Abstract: At the present time, there is a paucity of literature regarding medial meniscal posterior root repair and outcomes. This review seeks to examine the currently available data to further elucidate the clinical risks and benefits and any associated risks of medial meniscal posterior root repair. A systematic literature search was performed up to July 2018 in the databases of Medline via PubMed, EBSCOhost, and EMBASE. The results were reviewed independently by two authors and appropriate articles were reviewed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Similarly, significant improvements were found in 5 of 5 studies investigating HSS scores, with a mean improvement of 34.2 points, far greater than the MCID 23 of 8.72. Statistically significant improvements were found in 16 of 16 studies evaluating IKDC scores, and the mean change of 29.2 is substantially higher than the MCID 23 of 3.19 to 16.17. Tegner activity ratings demonstrated lower relative improvements, increasing from a mean 2.8 to 3.8 on a 10-point scale, which is not a high level of activity.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, significant improvements were found in 5 of 5 studies investigating HSS scores, with a mean improvement of 34.2 points, far greater than the MCID 23 of 8.72. Statistically significant improvements were found in 16 of 16 studies evaluating IKDC scores, and the mean change of 29.2 is substantially higher than the MCID 23 of 3.19 to 16.17. Tegner activity ratings demonstrated lower relative improvements, increasing from a mean 2.8 to 3.8 on a 10-point scale, which is not a high level of activity.…”
Section: Discussionmentioning
confidence: 81%
“…PMMRT repair provides a consistent clinical benefit. Of 24 studies, 23 reported that Lysholm scores demonstrated significant improvements, and the mean change of 30.7 compares favorably with the minimal clinically important difference (MCID) 23 of 10.1. Similarly, significant improvements were found in 5 of 5 studies investigating HSS scores, with a mean improvement of 34.2 points, far greater than the MCID 23 of 8.72.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews evaluating outcomes after MMPR repair have reported similar improvements in Lysholm scores to those of the current study of approximately 30 points. 8,19 The Tegner score showed a mean improvement of only 0.60 points, which does not reach the minimal detectable change for knee injuries. 16 The lack of a significant improvement in Tegner scores may be caused by meniscus root repair being performed in a primarily older patient population, consisting of participants less likely to possess high levels of preoperative activity.…”
Section: # Discussionmentioning
confidence: 86%
“…Meniscus root repair solely results in significantly satisfying clinical outcomes. 33,34 However, at the present time, there is a paucity of studies comparing the outcomes of solely OWHTO and OWHTO concomitant with meniscus posterior root repair, while a few studies showed that significant differences of the clinical and radiologic outcomes were not found between the procedures. 35,36 There is insufficient evidence to exclude the possibility that the meniscus root tear and meniscus root repair influenced the results of the present study.…”
Section: Discussionmentioning
confidence: 99%